Signaling Threat - Murphy, Mary C.; Steele, Claude M.; Gross, James J. (Psychological Science, 2007)
This study examined the cues hypothesis, which holds that situational cues, such as a setting's features and organization, can make potential targets vulnerable to social identity threat. Objective and subjective measures of identity threat were collected from male and female math, science, and engineering (MSE) majors who watched an MSE conference video depicting either an unbalanced ratio of men to women or a balanced ratio. Women who viewed the unbalanced video exhibited more cognitive and physiological vigilance, and reported a lower sense of belonging and less desire to participate in the conference, than did women who viewed the gender-balanced video. Men were unaffected by this situational cue. The implications for understanding vulnerability to social identity threat, particularly among women in MSE settings, are discussed.